Genetic studies on the reproductive performance of Soviet Chinchilla breed of rabbit under the agroclimatic conditions of North Eastern region - CHOUDHARY, H; GOSWAMI, R N; DAS, D; DAS, A; CHOUDHURY, R ROY (The Indian Journal of Animal Sciences, 2014)
Reproduction performance of Soviet Chinchilla breed of rabbit was studied under the agro-climatic conditions of Meghalaya, a hilly state of North Eastern India. Season of kindling exerted highly significant etfect (p<0.01) on gestation period. service period, kindling interval and litter weight at weaning. Dry season (February-April) was a favourable season for kindling in terms of reproductive efficiency. Heritability of different reproductive traits and their genetic and phenotypic correlations were also estimated.